Exercise-Induced Rhabdomyolysis - Case Study - Emilian TARCAU; Doru-Nicolae LUCACI; Ioan-Cosmin BOCA; Adrian Titus SERSENIUC URZICA (Romanian Journal of Physical Therapy, 2024)
Introduction: Rhabdomyolysis is a complicated medical condition characterized by the rapid breakdown of damaged or injured skeletal muscles. This syndrome can be caused by various factors, with the most common being trauma, prolonged immobilization, sepsis, and the use of drugs and alcohol. Purpose: the case study aims to highlight the importance of the correct diagnosis of the rhabdomyolysis syndrome and the implementation of an effective treatment plan to avoid repercussions on the patient, which can put his life in danger. Material and method: The case study took place over a period of six months, at the subject's home, where the examinations, recovery programs and diet plan were implemented. The subject is a 23-year-old student who practices three sports, including bodybuilding, from which the rhabdomyolysis syndrome was triggered after an intense leg workout. Assessment tools used: Schober Test, Chest amplitude measurement, Apley's scratch Test, and Fingertip-to-floor Test. Results: There is a significant difference between the first treatment session and the last one, the degree of independence has increased, the mobility of the upper and lower limbs is much improved, the pains are reduced, and the endurance to the effort is also increased. Conclusion: As a general conclusion, I can say that the effects of rhabdomyolysis can be treated and reduced with a personalized program of physical therapy and alternative therapies.